Study on the Impact on Health and Land Use During the Construction of National Highways: राष्ट्रीय राजमार्ग के निर्माण के दौरानः स्वास्थ्य एवं भूमि उपयोग पर प्रभाव का अध्ययन - Kumar, Kishan (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Any development plan or new construction project in the world has negative effects on the environment and human health. New inventions and constructions harm nature, which adversely impacts the environment. Therefore, it is said that human progress has detrimental effects on both nature and human health, which should be studied and efforts must be made to find solutions. Abstract in Hindi Language: विश्व में किसी भी विकास योजना अथवा नव निर्माण का मानव के पर्यावरण एवं स्वास्थ्य पर नकारात्मक प्रभाव पडता है। नये-2 अविष्कार एवं विनिर्माण से प्रकृति को आघात पहुंचता है जो पर्यावरण पर बुरा प्रभाव डालता है। इसलिए यह कहा जाता है कि मानव की प्रगति से प्रकृति एवं मानव स्वास्थ्य पर विपरीत प्रभाव पडता है जिसका अध्ययन एवं उसके समाधान के प्रयास होने चाहिए। Keywords: राष्ट्रीय, राजमार्ग, फेफडे, कृषि भूमि, भण्डारण, पेयजल, दूषित, ज्वलनशील